(untitled) (Baltic Journal of Sport and Health Sciences, 2021)
Background. The hypothesis of this study is formulated as follows: the experience of junior basketball players in competitions will be more valuable than that of cadet basketball players. The aim of our study was to examine the peculiarities of youth and basketball players’ sport experiences. Methods. A total of 104 basketball players, 47 cadets and 57 juniors participated in the study. Survey questionnaire is used for the study. The following methodologies were used: Athlete’s Personal Experience Survey (Athletic Coping Skills Inventory, ACSI-28) and the Sport Experiences Questionnaire (SEQ). Results. The results of the study revealed statistically significant differences (p <.05) in personal sport experiences (athletic endurance skills) among basketball players of different age groups according to the following indicators: the coach’s influence on basketball players, concentration, athletes’ self-confidence and resilience. The results of the study of athletes’ competitive experiences revealed that there were statistically significant differences (p <.05) between cadet and junior basketball players in competition experience. No statistically significant differences were found in terms of risk and progress parameters. Conclusions. The coach’s influence was greater for the cadet basketball players. Concentration, self-confidence and resilience were better among junior basketball players. This shows that when competing, junior basketball players have higher levels of concentration compared to the cadet group, as they are more confident and can better cope with tension. In addition, it was found that the experience of junior basketball players in competitions is richer than that of cadet basketball players. Keywords: sport experience, junior, cadet, basketball players, basketball.